Creative compliance and selective visibility: How Chinese queer uploaders performing identities on the Douyin platform - Ai, Qi; Song, Yuchen; Zhan, Ning (Media, culture & society, 2023)
The growth in video-sharing social media platform use has changed modes of communication, which has helped to improve the visibility of gender and sexual minority groups. This tendency became evident given the social distancing during the COVID-19 pandemic. Likewise, the use of these platforms empowers LGBTQ individuals living in China to share knowledge and experiences, receive social and emotional support and so on. Previous studies rarely interrogate Chinese queer groups’ socially sanctioned performance of identities on popular video-sharing platforms such as Douyin. This article undertakes a preliminary discussion of that research gap. It examines the conditions that enable such activities and concludes with a discussion of the strategies and methods that Chinese queer uploaders use in the process. Simply put, this article explores how the queer uploaders accommodate and negotiate their identity performances within a heterosexual and mainstream popular social media environment.